2014
DOI: 10.1074/jbc.m114.593855
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthetic Biscoumarins Target Tumor Necrosis Factor-α in Hepatocellular Carcinoma in Vitro and in Vivo

Abstract: Background: TNF-␣-induced NF-B pathway is associated with the progression of several cancers and abrogation of TNF signaling a potential target for cancer treatment. Results: Novel biscoumarin inhibits TNF signaling in vitro and in vivo in IBD model. Conclusion:The lead compound interrupts the trimeric structure of TNF to achieve this effect. Significance: This study introduces a novel TNF inhibitor with the potential to target pro-inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 56 publications
1
51
0
Order By: Relevance
“…this compound was obtained from 2-amino benzyl alcohol (1 mmol), 2-butyl-4-chloro-1-(4-nitrobenzyl)-1H-imidazole-5-carbaldehyde (1 mmol) and chloro acetic acid (2.5 mmol) in methanol at room temperature as a brown crystalline solid, yield 81%; melting point 53-55°C; elemental analysis calculated for C 22 (23), and 4-(7-chloro-2,4-dihydro-1H-benzo[d] [1,3]oxazin-2-yl)phenol (24) were prepared using the reported protocol.…”
Section: Synthesis Of 2-(2-butyl-mentioning
confidence: 99%
“…this compound was obtained from 2-amino benzyl alcohol (1 mmol), 2-butyl-4-chloro-1-(4-nitrobenzyl)-1H-imidazole-5-carbaldehyde (1 mmol) and chloro acetic acid (2.5 mmol) in methanol at room temperature as a brown crystalline solid, yield 81%; melting point 53-55°C; elemental analysis calculated for C 22 (23), and 4-(7-chloro-2,4-dihydro-1H-benzo[d] [1,3]oxazin-2-yl)phenol (24) were prepared using the reported protocol.…”
Section: Synthesis Of 2-(2-butyl-mentioning
confidence: 99%
“…PARP is an integral part of cellular DNA repair machinery and a target of caspase-3 and caspase-7. 30 Our western blotting results clearly suggest the cleavage of PARP from a 116 kDA protein into an 89 kDA fragment, evidencing that CPP induces apoptosis. We also found that CPP exert anticancer effects by inhibiting migration and invasion of HCC cells.…”
Section: Introductionmentioning
confidence: 55%
“…18,26,27 We found bisbenzimidazoles 5d and FDPB having p-methoxy-and p-flurosulfonyl groups exhibited significant cytotoxicity towards HeLa and HCT116 cells with the IC 50 values ranging from 16.7 lM to 19.9 lM. Further, bisbenzimidazoles 5b-c bearing tolyl and mesityl sulfonyl groups displayed notable anticancer activity with IC 50 values ranging from 20.1 lM to 41.6 lM against HeLa and HCT116 cells.…”
Section: Introductionmentioning
confidence: 80%